New Perspectives on Historical Research: The Digitization of the Documents of the AUSSME on the Peace of Versailles - Vagnini, Alessandro (Richtmann Publishing, 2012)
On November 11, 1918, the Great War that lasted for over four years came to a close. The peace treaties imposed by theEntente and Associated Powers after the War tried to establish a new international system. The research project â€œThe Europe ofVersailles (1919-1939). The new European balance between the two wars in the sources of the Archive of the Army General Staffâ€ isfunded by the Italian Ministry of University and Research (MIUR) under the program â€œFuturo in ricercaâ€ Firb 2010. It aims to examinespecifically the events that marked the First World War and the results of the Peace Conference of Versailles in Central and EasternEurope trough the digitization of the records of the archive of the Italian Army and the publication of several specific books.